Of muscles and men : essays on the sword and sandal film - Cornelius, Michael G. (Jefferson, N.C. : McFarland & Company, Inc., Publishers, 2011)
"Few movie genres have highlighted the male body more effectively than the "sword-and-sandal" film, where the rippling torso and the bulging muscle are displayed for all to appreciate. Carrying his ubiquitously phallic sword and dressed in traditional garb calculated to highlight his magnificent physique"--Provided by publisher.
Introduction: the functions and forms of the sword and sandal film / Michael G. Cornelius -- Hercules, politics, and movies / Maria Elena D Amelio -- Hero trouble: blood, politics, and kinship in Pasolini's Medea / Kristi M. Wilson -- To do or die manfully : performing heteronormativity in recent epic films / Jerry B. Pierce -- From maciste to maximus and company: the fragmented hero in the new epic / Andrew B. R. Elliott -- Reverent and irreverent violence: in defense of Spartacus, Conan, and Leonidas / John Elia -- Civilization- ancient and wicked : historicizing the ideological field of 1980s sword and sandal films / Kevin M. Flanagan -- Homer's lies, Brad Pitt's thighs: revisiting the pre-Oedipal mother and the German wartime father in Wolfgang Petersen's Troy / Robert C. Pirro -- An enduring logic: Homer, Helen of Troy, and narrative mobility / Larry T. Shillock -- By Jupiter's cock! Spartacus: blood and sand, video games, and camp excess / David Simmons -- Beefy guys and brawny dolls: He-Man, the Masters of the Universe, and Gay clone culture / Michael G. Cornelius -- Developments in peplum filmmaking: Disney's Hercules / Chris Pallant -- Hercules diminished? parody, differentiation, and emulation in the Three Stooges meet Hercules / Daniel O'Brien.
Includes bibliographical references and index.
boek